SYMBOLISM OF THE TABERNACLE IN THE COMPOSITION THREE STEPS OF HARMONY: A THEOLOGICAL SEMIOTIC AND CULTURAL STUDY - Klemens Siburian; Mauly Purba; Pulumun P Ginting; Vanesia Amelia Sebayang; Junita Batubara (Universitas Negeri Medan, 2026)
This article investigates the creative process and theological foundations of the musical composition Three Steps of Harmony, which is systematically constructed upon the symbolic tripartite structure of the Tabernacle of Moses in Pentecostal theology. Utilizing an artistic research approach—following Hawkins’ model of exploration, improvisation, and composition—integrated with Charles Sanders Peirce’s semiotic analysis, the study maps the spiritual journey from the Outer Court to the Most Holy Place onto fundamental musical elements: rhythm, melody, and harmony. The research addresses a gap in church music literature by moving beyond purely functional liturgical studies toward an analysis of music as an epistemic medium—a conceptual framework that organizes complex spiritual teachings. The composition is specifically situated within the cultural context of Pentecostal congregations in Medan, North Sumatra, where music is viewed as a